Challenges of Low Carbon City Planning due to Emissions from Brick Kilns: A Case Study on Dhaka City of Bangladesh (Journal of Bangladesh Institute of Planners, 2016)
In achieving environmental sustainability, planning of a city or region can be more functional and implementable by using low carbon city concept. Urban Planning through land use planning and planning control can play a vital role in implementing the idea of low carbon cities, particularly during the formulation of development plans. The study focuses on the issues of carbon emission and global warming due to emission from the brick fields of Dhaka in Bangladesh. The brick manufacturing in the Greater Dhaka region produces 3.5 billion bricks per year, and it has been estimated that about 23,300 tons of particulate matter having aerodynamic diameter